Synthesis and Characterization of Novel Benzimidazole Derivatives using CdO NPs and their Application as Antibacterial and Antifungal Agents - Asmaa M. Abdullah; Abdull Jabar Kh. Attia; Sergei N. Shtykov (Al-Mustansiriyah Journal of Science)
Background: Benzimidazoles are a class of compounds characterized by a fusion of benzene and imidazole rings. This unique structure endows them with a broad spectrum of biological activities, making them invaluable in medicinal and pharmaceutical research. The benzene ring provides aromatic stability, while the imidazole ring offers a site for various chemical modifications, enhancing their versatility and functionality. Benzimidazoles are known for their diverse pharmacological properties, including antimicrobial, antiviral, anticancer, anti-inflammatory, and antiparasitic. Objective: Synthesis of new benzimidazole derivatives and their application as antibacterial and antifungal agents. Methods: The benzimidazole derivatives (A1-A5) were synthesized in high yields by condensing 2-(4-hydroxyphenyl) benzimidazole with different aldehydes (p- nitro benzaldehyde and p- bromo benzaldehyde) and amides (benzamide and acetamide) utilizing cadmium oxide nanoparticle (CdO NPs) as a catalyst. Results: The synthesized benzimidazole derivatives (A1-A5) were characterized using FTIR and 1HNMR spectra, and showed good antibacterial activity (inhibition zone: 5-23 mm) with various concentrations (250, 500, and 1000 mg/L) while the compounds (A1, A3, A4, and A5) also exhibited moderate antifungal activities (inhibition zone: 5-10 mm) except the A2 compound. Conclusions: The antimicrobial and antifungal effectiveness of these synthesized derivatives was evaluated, showing satisfactory antimicrobial activity and suitable antifungal activity for all except the A2 compound. It is recommended that further research and structural modifications of these derivatives be conducted to develop more potent benzimidazole derivatives.